2018
DOI: 10.1200/jgo.18.00053
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs, and Attitudes About Breast Cancer Screening in Latin America and the Caribbean: An In-Depth Narrative Review

Abstract: PurposeBreast cancer (BCA) is the most common cancer and leading cause of cancer mortality among women in Latin America and the Caribbean (LAC), and the number of deaths from BCA is expected to continue to increase. Although barriers to care include the physical accessibility of screening resources, personal and cultural barriers must be explored to understand necessary next steps to increase access to preventive care. The purpose of this in-depth narrative literature review was to explore empiric literature t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…The majority of these deaths can be prevented through HPV vaccination for girls and screening for precancerous lesions for women at risk (Hasahya et al, 2016;Jradi and Bawazir, 2019). Prevention and control interventions against breast cancer have been implemented well in developed countries, so there has been a decrease in cases and detected death rates over the past three decades (Doede et al, 2018;Heena et al, 2019). This is different in developing countries such as Indonesia where there is still low awareness of women to screen for cervical cancer and breast cancer (Endarti et al, 2018;Endriyani et al, 2017;Rio and Suci 2017;Solikhah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these deaths can be prevented through HPV vaccination for girls and screening for precancerous lesions for women at risk (Hasahya et al, 2016;Jradi and Bawazir, 2019). Prevention and control interventions against breast cancer have been implemented well in developed countries, so there has been a decrease in cases and detected death rates over the past three decades (Doede et al, 2018;Heena et al, 2019). This is different in developing countries such as Indonesia where there is still low awareness of women to screen for cervical cancer and breast cancer (Endarti et al, 2018;Endriyani et al, 2017;Rio and Suci 2017;Solikhah, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review including 35 articles concerning beliefs and attitudes towards breast cancer screening in Latin America concluded that, apart from resources and personnel, ‘competent community educational interventions across all aspects of breast cancer’ are vital to ensure a successful population screening programme. 24 In some LMICs, the lack of breast cancer awareness could cause a 29-month delay on average in medical care after self-detecting a breast lump, which resulted in diagnoses at more advanced stages. 25 Therefore, a screening programme with a strong educational component is key to ensure high participation rates in Argentina.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of the staff's clinical experiences also proved to be a barrier for test acceptance. 24 These unmet needs are magnified by the current COVID-19 pandemic where cancer diagnostics and surgery have been disrupted by the response to the pandemic with reduction in survival rates of 13% (stage II) and 18% (stage III) as a consequence. 26 Telemammography, usually having smaller, less crowded centres separated from hospitals, can be a way of reducing exposure to the virus while continuing screening.…”
Section: Barriers To Implementing a Breast Cancer Screening Programmementioning
confidence: 99%
“…A study in 1996 conducted in the chiefly African-populated island of Tobago (the smaller island) where no mammography services were available at the time found low levels of self as well as clinical breast examinations largely due to the unavailability of programs for early detection (66% of respondents), cost of screening (52%), no direct access to mammograms with the hassle of traveling to Trinidad for screening (66%), and fear of cancer (48%) [ 108 ]. Trinidadians are now more aware of the need for regular screening and over 90% are willing to have repeat mammograms, though less than 50% knew that mammograms are not always capable of detecting cancer [ 86 , 109 ]. A study in 2014 conducted in South Trinidad, with a more diverse study population, found much higher compliance with routine self-breast examinations, and education and family history of breast disease were strongly associated with a better attitude towards mammography usage [ 86 ].…”
Section: Reviewmentioning
confidence: 99%
“…Self-examination has been proven to be essential with an alarming 91.6% (245/268) of BC cases in a Trinidad and Tobago study population detected via this routine procedure [ 64 ]. However, Trinidadians reported that fear of finding cancer discouraged screening [ 86 , 108 , 109 ].…”
Section: Reviewmentioning
confidence: 99%